Pengaruh Profitabilitas dan Capital Expenditure terhadap Cash Holding pada Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia - Tri Putri Erawati; Muhammad Iqbal Pribadi; Rahman Anshari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the impact of profitability and capital expenditure on cash holding ownership in companies engaged in the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. This study applied a quantitative approach by utilizing secondary data as many as 321 observations were used in the study, which came from 107 selected companies using purposive smapping. The data analysis process is carried out using the panel data management method. Based on the results of the model selection test carried out, the appropriate approach is the Fixed Effect Model. The findings of this study show that profitability measured through return on assets (ROA) has a positive and significant influence on cash holding. On the other hand, capital expenditure proxied with the CAPEX value shows a negative and significant influence on the cash holding owned by the company.